2018
DOI: 10.31235/osf.io/azwsb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Fragmented Evolution of Racial Integration since the Civil Rights Movement

Abstract: Abstract:We argue that existing studies underestimate the degree to which racial change leads to residential segregation in post-Civil Rights American neighborhoods. This is because previous studies only measure the presence of racial groups in neighborhoods, not the degree of integration among those groups. As a result, those studies do not detect gradual racial succession that ends in racially segregated neighborhoods. We demonstrate how a new approach based on growth mixture models can be used to identify p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 14 publications
(19 reference statements)
2
50
1
Order By: Relevance
“…The effects of residential mobility on segregation, however, need to be understood in relation to demographic developments (e.g., Bader & Warkentien, ; Simpson et al, ). The population composition of neighbourhoods can change without in‐ and out‐migration.…”
Section: Ethnic Neighbourhood Changementioning
confidence: 99%
“…The effects of residential mobility on segregation, however, need to be understood in relation to demographic developments (e.g., Bader & Warkentien, ; Simpson et al, ). The population composition of neighbourhoods can change without in‐ and out‐migration.…”
Section: Ethnic Neighbourhood Changementioning
confidence: 99%
“…Numerous studies using different methods have reported a decline in all-white neighborhoods and increasing diversity at the neighborhood level (Farrell and Lee 2011, Brown and Sharma 2010, Iceland and Sharp 2013, Lee, Iceland and Farrell 2014, Parisi, Lichter and Taquino 2015, Ellen, Horn, and O’Regan 2012, Bader and Warkentien forthcoming). The specific category of global neighborhood, however, is only one form that diversity can take.…”
Section: Metropolitan Contexts For Neighborhood Changementioning
confidence: 99%
“…Not only did Jim Crow laws finally fall, but Whites, as in many cities, began to relocate to the suburbs by the tens of thousands. As they did, Black and Latino populations grew in number and spread throughout established neighborhoods of the urban core (Bader and Warkentien ; Korver‐Glenn and Elliott ). In the process, Houston — a city well‐known for having no official zoning — became even more of the expanding, unplanned frontier it had long seemed to outsiders.…”
Section: Houston: From Master Plan Onwardmentioning
confidence: 99%